ANALISIS BRAND TRUST DAN BRAND ROYALTY KONSUMEN GARUDA INDONESIA - Khoza, Kevin; Harjati, Lily (MAJALAH ILMIAH WIDYA, 2012)
Many airlines offer cheap fares and good service which makes Garuda Indonesia should be prepared to face the tight competition.In order to overcome the problem, one way is to build consumer trust to the brand Garuda Indonesia. Brand trust is expected to bethe brand loyalty or customer loyalty to Garuda Indonesia. The purpose of this paper is to analyze the brand trust and brand loyaltyin consumers of Garuda Indonesia. The research is based on the theory of brand trust and brand loyalty and used survey by distributionquestionnaires. The collected data was analyzed.descriptively.The results showed that the consumers of Garuda Indonesia Airlinetrust and loyal to Garuda Indonesiaâs brand.